ANALISIS PENGARUH LUXURY VALUE PERCEPTION DAN ETHICAL CONCERN TERHADAP PURCHASE INTENTION DALAM PEMBELIAN PERHIASAAN EMAS DAN PERAK DI DENPASAR - Ni Made Hartini; Putu Soviyanti (Journal of Applied Management Studies, 2022)
This study aims to analyze the influence of Luxury Value Perception and Ethical Concern on Purchase Intention in the purchase of gold and silver jewelry in Denpasar. This research includes a type of confirmatory research, which will explain the causal relationship between independent variables and dependent variables through hypothesis testing. The data used in this study are primary data. The primary data obtained was obtained directly from the questionnaire that had been filled out by respondents, namely people domiciled in Denpasar. The data collection method used in this study was the questionnaire method. The data analysis techniques used in this study are descriptive statistics and Second Order Partial Least Square (PLS) analysis techniques with the Smart PLS Program. The results of the hypothesis testing carried out showed that (1) there was a significant influence between Luxury Value Perception and Purchase Intention; (2) Ethical Concern has a significant influence on Purchase Intention. The implication in this study is that Purchase Intention can be achieved with Luxury Value Perception and Ethical Concern. Meanwhile, the conclusions obtained from the results of this study are (1) Luxury Value Perception has a significant effect on Purchase Intention; (2) Ethical Concern has a significant influence on Purchase Intention on the purchase of gold and silver jewelry in Denpasar.